WOOD DRYERS: A SUSTAINABLE ALTERNATIVE FOR INCREASED CHARCOAL PRODUCTION - Figueiró, Clarissa Gusmão; Carneiro, Angélica de Cássia Oliveira; Fialho, Lucas de Freitas; Magalhães, Mateus Alves; Ribeiro, Gabriel Browne de Deus; Ferreira, Fernanda Barbosa (Floresta, 2019)
The aim of the study was to evaluate the technical and economic viability of a wood dryer in the charcoal production. Drying was carried out for 72 hours using wood from Eucalyptus sp. in two classes of diameter. The average admission temperature of combustion gases in the dryer was 100-150ºC. It was determined the mass of water withdrawn by drying and estimated the amount of wood that would be consumed during the pyrolysis to remove the same amount of water, being this wood converted into charcoal mass. In the economic analysis were determined the indicators net present value, internal rate of return and discounted payback. The dryer presented technical feasibility, reducing wood moisture by 8% and, consequently, increasing the charcoal productivity by 3.3%, and economic viability, with good financial indicators for current market conditions, including a discounted payback of 6 years. In this way, the use of a wood dryer was presented as an efficient way to take advantage of an environmental liability of pyrolysis, which contributes to the increase of sustainability in the charcoal production.